Design of power converters with embedded energy storage for hybrid DC-AC applications - Neira Castillo, Sebastián (The University of Edinburgh, 2023)
The high penetration of renewable energies into power systems is leading to a revolution in the structure of modern power grids. In this context, the present thesis investigates the design of power electronics converters with extended capabilities due to the embedding of energy storage within the topologies. Thus, the research objective is to propose power converters with capabilities of integrating energy storage technologies to provide further services required for the operation of hybrid dc-ac systems. The thesis contains two parts, first part shows the work developed for low- and medium-power applications, while the second part describes the investigation performed for high-power systems. The first part of this thesis explains the design and operation of a three-port dc-dc-ac converter developed for integrating energy storage into hybrid dc-ac applications. The topology is based on a conventional two-level dc-ac converter, and it uses a single power conversion stage to control the power flow between three ports, minimising the required components. Simulation and experimental results validate the operation of the proposal, showing that a multi-variable control system allows exploiting the degrees of freedom to manage power interactions of multiple elements without needing extra power converters. Furthermore, a comparative analysis is carried on to showcase the advantages and limitations of the proposal as opposed to state-of-the-art solutions in the same context. The study concludes that the proposed topology is suitable for low- and medium-power systems with bidirectional power flow capabilities among all ports and limited voltage boost needs. Simulation analysis shows that efficiencies up to 95.94% can be reached for a 3 kW design, which compares to efficiencies of similar state-of-the-art topologies. Moreover, the operation is also validated in a reduced-scale prototype allowing to test the multi-variable control scheme in a real-time implementation. The second part of the thesis focuses on the design and operation of a Modular Multilevel Converter (MMC) topology with integrated energy storage using new parallel branches in the phases of the converter. This topology allows the integration of partially-rated Energy Storage Systems(ESS) to decouple the ac and dc sides of a High Voltage Direct Current~(HVDC) substation. Thus, it enables the provision of ancillary services such as fast frequency response, black-start capabilities and load-levelling, which are required by modern hybrid dc-ac power grids. Results show that the proposal allows the addition of up to 37% power from the ESS considering similarly rated power semiconductors in a simulated 1 GW MMC substation. Analysis shows that extra device losses remain under 1% for an additional +-10% of ESS power on top of the nominal substation-rated power. Furthermore, a laboratory-scale experimental rig was built to demonstrate the operation of the proposed design. In conclusion, two different topologies are proposed and analysed for integrating energy storage into hybrid dc-ac applications depending on the power rating required. The study is supported by simulation and experimental results obtained during the project to validate both proposals.
Keywords: DC-AC power conversion; multi-port converters; Modular Multilevel Converters (MMC); Energy Storage Systems (ESS); hybrid power integration; multi-variable control systems